2018
DOI: 10.5944/openpraxis.10.3.866
|View full text |Cite
|
Sign up to set email alerts
|

Are Private Universities Exempt from Student Concerns About Textbook Costs? A Survey of Students at American University

Abstract: A survey conducted in the fall of 2015 at American University in Washington, DC shows that rising textbook prices similarly affect students at an expensive private university as those at community colleges and state schools. Research on high textbook costs that has demonstrated corollary unwanted behavior changes in students, including not purchasing the book, resorting to illegal online downloads, and poor study habits, were confirmed at American University as well. Solutions that have been proposed to this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The Florida reports are the one of the largest open sources of textbook use data, including self-reported expenditures, from U.S. students in higher education. They are commonly referenced by other textbook survey authors (Jhangiani & Jhangiani, 2017;Martin et al, 2017;Tillinghast, 2017;Murphy & Rose, 2018;Wittkower & Lo, 2020). However, because the Florida studies surveyed students at public colleges and universities across the state-a population with significant differences from our own student body-we observed hesitation from faculty regarding the relevance of the results on our own campus.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The Florida reports are the one of the largest open sources of textbook use data, including self-reported expenditures, from U.S. students in higher education. They are commonly referenced by other textbook survey authors (Jhangiani & Jhangiani, 2017;Martin et al, 2017;Tillinghast, 2017;Murphy & Rose, 2018;Wittkower & Lo, 2020). However, because the Florida studies surveyed students at public colleges and universities across the state-a population with significant differences from our own student body-we observed hesitation from faculty regarding the relevance of the results on our own campus.…”
Section: Introductionmentioning
confidence: 95%
“…In a survey by Murphy and Rose at American University also conducted in 2015, 45% of respondents spent over $300 on textbooks in Fall 2015, and 67% of respondents said that they had decided not to purchase a textbook due to cost (Murphy & Rose, 2018). When students at Brigham Young University were surveyed in 2016, 66% reported that they had chosen not to purchase a textbook due to cost, and 47% of those reported that it had negatively affected their grades (Martin et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the majority of faculty believe textbook costs are too high and that this is a significant concern for students (Jaschik & Lederman 2018;Seaman & Seaman 2019). Commercially available textbooks have also been shown in multiple environments to cause stress and result in students failing to purchase or delaying purchasing materials necessary to be successful (Jenkins et al 2020;Jhangiani & Jhangiani 2017;Martin et al 2017;Murphy & Rose 2018). The impact on students is often personal as well as academic.…”
Section: Access Barriers Related To Textbook Costs Financial and Psychological Impact On Studentsmentioning
confidence: 99%
“…In numerous surveys, students have reported that the rapidly growing price of textbooks impacts them significantly (Christie et al, 2009;Florida Virtual Campus, 2018;Murphy & Rose, 2018;Senack & Donoghue, 2016). The average undergraduate will spend around $5,000 on textbooks over four years and this cost is frequently covered by student loans, increasing the debt that they carry (Ma et al, 2018;Senack & Donoghue, 2016).…”
Section: The Problemmentioning
confidence: 99%